Solidification Behavior and Microstructure of Al-7Si Alloys with Individual and Combined Additions of Sr and Yb - Zhou Dong; Zhi Hu; Hong Yan; Hecong Xie; Xiao Li (Advances in Materials Science and Engineering)
The effects of individual and combined additions of Sr and Yb on the solidification behavior and microstructure of Al-7Si alloys were investigated using thermal analysis, optical microscopy, and scanning electron microscopy. The results showed that the nucleation temperature, minimum temperature, and growth temperature of eutectic solidification were lower than those of the unmodified alloys, and eutectic recalescence at 2°C in the Yb- and (Sr + Yb)-modified alloys was observed. The decrease in the nucleation temperature and an increase in recalescence obviously refined the eutectic Si morphology of the Sr-, Yb-, and (Sr + Yb)-modified alloys from a coarse plate-like structure to a fine fibrous structure. Moreover, the three-dimensional microstructure of eutectic Si in the (Sr + Yb)-modified alloy showed the finer fibrous structure, which was mainly attributed to formation of the Al2Si2Yb phase. The formation enthalpy of Al2Si2Yb was lower than that of Al-(Si)-Sr in the (Sr + Yb)-modified alloy, thus suppressing the formation of the Al2Si2Sr intermetallic compound. The more effective Sr together with Yb further improved the modification effect of eutectic silicon.